Smart Farming: Challenges and Adoption Factors among Paddy Farmers in IADA Barat Laut, Selangor - Saili, Abdul Rahman; Kamarul Zaman, Nur Badriyah; Mohd Noor, Wan Noranida Wan; Abdul Fatah, Fazleen; Abdullah, Farah Adila (Information Management and Business Review, 2024)
Enhancing farm production through smart farming technology is crucial for addressing the challenges of achieving food security and improving the well-being of farmers. Aligned with Sustainable Development Goal 2 (SDG2), which is intended to tackle food insecurity and malnutrition while improving livelihood, smart farming integrates technologies such as IoT, drones, and artificial intelligence into agricultural practices. This innovation optimizes input like water, fertilizer, and pesticide, reduces operation costs, and increases productivity and profits. Food security in Malaysia is measured based on the adequacy of the population’s domestic rice supply. Smart farming offers a transformative approach to modern agriculture, focusing on increasing value while reducing costs. Therefore, this study aims to explore challenges and adoption factors among paddy farmers in Barat Laut Selangor, under the administration of the Integrated Agriculture Development Area (IADA). An exploratory qualitative study involved the interview approach with selected rice farmers who applied smart farming as suggested by IADA. The thematic analysis was used to understand the factors that contribute to the adoption of smart farming among rice farmers and its challenges. This research is critical, given Malaysia is moving towards a high-income country, where sustainability becomes the main agenda in any sector specifically agriculture; and the country has acknowledged the importance of food security assurance. By identifying the challenges and adoption factors, this study aims to provide actionable insights to support sustainable agricultural practices and strengthen Malaysia’s food security framework.